Pelembagaan Hukum Islam di Sumatera Timur: Tinjauan Historis - Nasution, Jumanah; Fuad, Zainul (Universitas Ekasakti, 2023)
The institutionalization of Islamic law has long roots in the life history and collective memory of the Indonesian Muslim community; Reflected in various proverbs such as